2019
DOI: 10.1186/s12911-019-0887-8
|View full text |Cite
|
Sign up to set email alerts
|

What do healthcare professionals need to turn risk models for type 2 diabetes into usable computerized clinical decision support systems? Lessons learned from the MOSAIC project

Abstract: Background To understand user needs, system requirements and organizational conditions towards successful design and adoption of Clinical Decision Support Systems for Type 2 Diabetes (T2D) care built on top of computerized risk models. Methods The holistic and evidence-based CEHRES Roadmap , used to create eHealth solutions through participatory development approach, persuasive design techniques and business modelling, was adopted in the MOSAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Focus groups can be used in a sequential way: multiple focus groups can be conducted in a row and the goal and content of each focus group can be based on the outcomes of the previous focus groups. However, this iterative approach was said to be quite time consuming for researchers and participants [ 33 , 54 , 64 , 82 , 84 - 86 , 90 , 92 ]. Third, to ensure that valuable information for eHealth development is gathered, the content and form of focus groups need to be adapted, based on the topic and target group [ 39 - 41 , 51 , 55 , 61 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Focus groups can be used in a sequential way: multiple focus groups can be conducted in a row and the goal and content of each focus group can be based on the outcomes of the previous focus groups. However, this iterative approach was said to be quite time consuming for researchers and participants [ 33 , 54 , 64 , 82 , 84 - 86 , 90 , 92 ]. Third, to ensure that valuable information for eHealth development is gathered, the content and form of focus groups need to be adapted, based on the topic and target group [ 39 - 41 , 51 , 55 , 61 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, multiple authors indicated that usability tests should be conducted with a broad range of stakeholders: not only end users such as patients, but also caregivers, managers, technology developers, and experts on content and design [ 21 , 43 , 54 , 64 , 77 , 112 , 127 , 131 , 152 , 155 ]. Different types of participants can provide different kinds of feedback on an eHealth technology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current evaluation of ML-MEDIC is limited to more of a qualitative assessment of the benefit of GUI-based, user-interactive tools by the clinical community to facilitate and improve the use of ML in clinical applications. Further testing and quantitative analysis is needed to assess resources such as ML-MEDIC and the potential for use in clinical decision support and various clinical research applications [ 31 ].…”
Section: Discussionmentioning
confidence: 99%